The Influence of Financial Reward And Non-Financial Reward On Job Performance Mediated By Job Satisfaction At PT. X - Adinda Rachel Donda Hotnida L. Tobing (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Employees are the most valuable assets within a company or organization, as they serve as one of the driving forces in achieving the company’s goals based on its vision and mission. Therefore, companies need to pay attention to various aspects of human resource management within their organizations. This study uses several variables, namely financial reward, non-financial reward, job satisfaction, and job performance. The method used in this study is non-probability sampling with a saturated sampling approach. This research was conducted on all employees at PT. X who met the criteria defined by the researcher, and the data were collected through online questionnaires to facilitate the data collection process. Data analysis was carried out using the Structural Equation Modelling (SEM) method with the PLS-SEM application.The results of this study indicate that some variables have significant effects while others do not. Financial reward does not significantly influence job satisfaction or job performance, including through its mediating pathway. In contrast, non-financial reward has a significant effect on job satisfaction and also contributes to job performance through the existing mediating pathway in PT. X